2011
DOI: 10.1073/pnas.1102985108
|View full text |Cite
|
Sign up to set email alerts
|

Reshuffling genomic landscapes to study the regulatory evolution of Hox gene clusters

Abstract: The emergence of Vertebrata was accompanied by two rounds of whole-genome duplications. This enabled paralogous genes to acquire novel functions with high evolutionary potential, a process suggested to occur mostly by changes in gene regulation, rather than in protein sequences. In the case of Hox gene clusters, such duplications favored the appearance of distinct global regulations. To assess the impact of such "regulatory evolution" upon neofunctionalization, we developed PANTHERE (PAN-genomic Translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The genes involved are exemplar developmental genes present at the HOXA (human HOXA1-A7; Figure 2B) and HOXD (human HOXD1-4) clusters. Both clusters are implicated in multiple cancers and other disorders, and are tightly regulated via higher order chromatin domains [38], [39]. It is thought that structural divergence within the chromatin domains harbouring these clusters underlies many important innovations in the vertebrate body plan [40].…”
Section: Resultsmentioning
confidence: 99%
“…The genes involved are exemplar developmental genes present at the HOXA (human HOXA1-A7; Figure 2B) and HOXD (human HOXD1-4) clusters. Both clusters are implicated in multiple cancers and other disorders, and are tightly regulated via higher order chromatin domains [38], [39]. It is thought that structural divergence within the chromatin domains harbouring these clusters underlies many important innovations in the vertebrate body plan [40].…”
Section: Resultsmentioning
confidence: 99%
“…B) (Zákány et al, ; Spitz et al, ; Andrey et al, ). As in the spinal cord and somites, the proximity to the long‐range cis‐acting elements rather than promoter specificity defines the levels of Hox gene activation in developing limbs (Tarchini and Duboule, ; Montavon et al, ; Tschopp et al, ). The chromosome conformation capture on chip (4C) technique (Splinter et al, ) revealed that the transcriptionally active Hoxd11‐9 genes interact predominantly with the telomeric gene desert in proximal limbs (Fig.…”
Section: Cis‐regulatory Elementsmentioning
confidence: 99%
“…In one example, using a novel approach in which a targeted translocation was induced in the mouse genome, 104 Duboule's group placed the HoxC gene cluster under the regulatory control of the HoxD genomic locus and tested its ability to rescue HoxD loss-of-function phenotypes, which include defects in digit formation. 105 Their studies showed the HoxC cluster was largely able to rescue HoxD mutants, providing a compelling example of the importance of regulatory evolution within Hox complexes. Thus, after the duplication of Hox complexes in vertebrates, redundancy permitted diversification of highly related paralogs.…”
Section: Cis-regulatory Changes In Vertebrate Hox Complexesmentioning
confidence: 99%